Correlation between global damage and local damage of RC frame structures under strong earthquakes. Issue 3 (19th May 2016) - He, Zheng; Xu, Yichao
Summary: In order to reasonably incorporate local and global monitoring response data into dynamic update in the weighted combination models for a closer correlation between global damage and local damage, a logical time‐variant correlation between global damage and local damage is established for reinforced concrete structures under strong earthquakes. Two sets of dynamic weight coefficients used to characterize the relative damage contribution of floors through modal information and energy information are suggested in the correlation. The modal information‐based weight coefficients that are defined as the normalized accumulative times of reserved floors could be capable of retaining the necessary information of relatively weak floors or sensitive regions with localized damage significance, while the energy information‐based weight coefficients based on the normalized curvature difference of 'jerk energy' are helpful to quantify the relative degree of floor damages accumulated by hysteretic dissipated energy. The combination factors corresponding to the proposed dynamic weight coefficients, together with static weight coefficients, are calibrated by a macroscopic global seismic damage model. The results from the example study indicate that these factors show different changing rules with increasing peak ground acceleration level. Modal information‐based weight coefficients have been found to have a desirable agreement with the inter‐story pure translation ratios. Copyright © 2016 John Wiley & Sons, Ltd.